Marketing for sustainability : towards transactional policy-making - Bartels, Gerard, 1947-; Nelissen, Wil (IOS ; Ohmsha, 2002)
This work deals with the marketing and communication of government institutions, non-profit organizations and profit organizations that make up the challenge of sustainable development. Each chapter deals with marketing and (mass) communication.